2021
DOI: 10.3389/fimmu.2021.671511
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Alleviates Murine Experimental Autoimmune Encephalomyelitis by Triggering Autophagy in the Spinal Cord

Abstract: Multiple Sclerosis (MS) is a neuroinflammatory and chronic Central Nervous System (CNS) disease that affects millions of people worldwide. The search for more promising drugs for the treatment of MS has led to studies on Sildenafil, a phosphodiesterase type 5 Inhibitor (PDE5I) that has been shown to possess neuroprotective effects in the Experimental Autoimmune Encephalomyelitis (EAE), an animal model of MS. We have previously shown that Sildenafil improves the clinical score of EAE mice via modulation of apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Sildenafil has been found to enhance neurogenesis and synaptic plasticity through the activation of the PI3K/Akt pathway in adults ( Peixoto et al, 2015 ) and neonates ( Yazdani et al, 2021 ). In a mice model of autoimmune encephalomyelitis, sildenafil inhibited microglia activation and the death of oligodendrocytes through the mitogen-activated protein kinase (MAPK) signaling pathway ( Duarte-Silva et al, 2018 , 2021 ). PKG also increased the production of inflammatory cytokines [interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor alpha (TNF-α), etc.…”
Section: Mechanisms Of Action Of Sildenafilmentioning
confidence: 99%
See 1 more Smart Citation
“…Sildenafil has been found to enhance neurogenesis and synaptic plasticity through the activation of the PI3K/Akt pathway in adults ( Peixoto et al, 2015 ) and neonates ( Yazdani et al, 2021 ). In a mice model of autoimmune encephalomyelitis, sildenafil inhibited microglia activation and the death of oligodendrocytes through the mitogen-activated protein kinase (MAPK) signaling pathway ( Duarte-Silva et al, 2018 , 2021 ). PKG also increased the production of inflammatory cytokines [interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor alpha (TNF-α), etc.…”
Section: Mechanisms Of Action Of Sildenafilmentioning
confidence: 99%
“…In a rat model of irradiation-induced brain injury, sildenafil showed anti-inflammatory and antioxidant properties through the modulation of the NO/tetrahydrobiopterin (BH4) pathway ( Thabet et al, 2021 ). In addition, in a model of experimental autoimmune encephalomyelitis (EAE), sildenafil appeared neuroprotective by promoting the switch of microglia from the proinflammatory M1 phenotype to the anti-inflammatory M2 phenotype ( Pifarré et al, 2014 ), which reduced the infiltration of CD4+ T lymphocytes and the production of IL-17 and TNFα ( Araújo et al, 2020 ), and activated autophagy ( Duarte-Silva et al, 2021 ).…”
Section: Effects Of Sildenafil On Neuroinflammationmentioning
confidence: 99%
“…By using the NO scavenger UA [ 21 ], we found that elevation of NO levels in NHF upon TOP-N53 appear in part responsible for autophagy activation. Moreover, when we treated NHF with the potent PDE5-specific inhibitor sildenafil, we corroborated that PDE5 inhibition induced a similar response to TOP-N53, resulting in autophagy activation [ 22 ]. Thus, both TOP-N53-induced mechanisms appear to contribute to an activation of autophagy, which is likely due to an increase in P 62 transcription.…”
Section: Discussionmentioning
confidence: 67%
“…Sildenafil is a specific PDE5 inhibitor blocking cGMP breakdown and mimicking the effects of TOP-N53 due to the inhibition of PDE5 only. Sildenafil was recently shown to activate autophagy in an experimental mouse model of autoimmune encephalomyelitis [ 22 ]. As TOP-N53, sildenafil led to an increase in P 62 mRNA levels ( Figure 5 c).…”
Section: Resultsmentioning
confidence: 99%
“… 38 , 39 In addition, its up‐regulation promoted the inflammatory responses. 40 , 41 Meanwhile, it has been reported that activation of CREB lead to the development of atherosclerosis. 18 , 42 However, the effect of EP3 on CREB expression during the development of atherosclerosis remains unclear.…”
Section: Discussionmentioning
confidence: 99%